2021
DOI: 10.3390/foods10123157
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Microbiological, and Sensorial Quality Attributes of a Fermented Milk Drink (Laban) Fortified with Date Syrup (Dibs) during Cold Storage

Abstract: This study investigated the nutritional, microbial, and sensory quality attributes of a fermented milk (laban) drink flavored with date syrup (dibs) during cold storage at 4 °C for 7 days. Date syrup was added to laban in specific proportions (2.5, 5, 7.5, 10, 12.5, and 15% date syrup/total weight of flavored laban) and an appropriate percentage (12.5%, 74 °Bx) was selected based on the sensory preference of panelists. The results indicate that flavoring laban with date syrup affected the physicochemical, nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Fermented milk products are important staples in Southern Mediterranean countries (Table 2). They are produced using milk from cows, goats, ewes, sheep, camels, or buffalo, depending on the country's livestock farming [26]. According to their consistency, two categories might be identified, i.e., drinkable yogurt and spoonable yogurt.…”
Section: An Overview Of the Traditional Fermented Milksmentioning
confidence: 99%
“…Fermented milk products are important staples in Southern Mediterranean countries (Table 2). They are produced using milk from cows, goats, ewes, sheep, camels, or buffalo, depending on the country's livestock farming [26]. According to their consistency, two categories might be identified, i.e., drinkable yogurt and spoonable yogurt.…”
Section: An Overview Of the Traditional Fermented Milksmentioning
confidence: 99%
“…Flavored Laban incorporated with date syrup showed an increase in pH, ash, protein, total solids, sugars, and magnesium whilst acidity, fat, casein, lactose, calcium, total microbial count, and total yeast and molds count decreased at the end of the study. Sensory evaluation revealed that the flavored Laban drink was more acceptable than the control samples after 7 days of cold storage [ 86 ]. In a more recent study, Shahein et al [ 87 ] produced probiotic fermented camel milk with date syrup as a prebiotic and flavoring agent to evaluate its physicochemical, phytochemical, microbiological, and sensory properties after 1 day and 15 days of storage at 5 °C.…”
Section: Application Of Date Fruits Products and Co-products In Foodsmentioning
confidence: 99%
“…Some other nutritionally vital constituents are found in date syrup, including dietary fiber, vitamins C and B-complex, and antioxidants such as polyphenols, flavonoids, and carotenoids. Its health benefits are diverse in its effects on body metabolism, such as antimicrobial, antimutagenic, immunostimulant, hepatoprotective, nephroprotective, gastroprotective and anti-hyperlipidemic properties . At the research level and commercial level, date syrup has been fortified and added in various food products such as functional yogurt, dough and bread, fermented milk drinks, processed cheese, rabri milk drink, probiotic dairy desserts and different backed goods and drizzled over ice cream, oatmeal, yogurt, French toast, pancakes, or even savory bites, such as a grilled cheese sandwich. In Arabic countries, date syrup in an essential cooking ingredients in various native dishes and added to improve the flavor of poultry, meat, fish, vegetables, pasta and rice. It is also drizzled over cheesecakes, cream cakes, toast, croissants, bagels, pancakes, sorbets, crepes and shakes .…”
Section: Vegan Sweetenersmentioning
confidence: 99%